Clinical characteristics and mortality in all Czech patients after pacemaker implantation in the last decade - Táborský, Miloš; Skála, Tomáš; Dušek, Ladislav; Kautzner, Josef; Aiglová, Renata; Fedorco, Marián; Jarkovský, Jiří; Benešová, Klára; Májková, Petra (Frontiers in cardiovascular medicine, 2023)
BACKGROUND AND AIMS: Analysis of mortality from the national health registries and data from a specific central registry dealing with the implantation of pacemakers (REPACE) in Czech patients. METHODS AND RESULTS: Retrospective observational analysis of pacemakers' implantation in all Czech patients [n = 82,791; 47,070 (56.9%) men, 75.9 ± 10.4 years old] between 2010 and 2021. Almost 114,000 pacemakers were implanted between 2010 and 2021, of which 27.9% were single-chamber, 67.4% were dual-chamber and 4.6% were biventricular. The annual number of implantations has been steadily increasing with a 6% annual decline in 2020 with increased mortality and reductions in care provided, likely related to COVID-19. The observed 5-year relative survival was 88.6% (overall survival 60.6%) and the 10-year relative survival was 75.9% (overall survival 32.7%). Causes of death 5ary according to the age of the patient. The highest difference 1n the reported numbers in the REPACE Registry did not exceed 2% in comparison with the National Register of Reimbursed Health Services. CONCLUSION: This study followed all Czech patients with pacemaker's implantation in between 2010 and 2021. The annual number of 1mplantations has been steadily 1ncreasing. Patients with implanted pacemakers had a significantly higher mortality than the average population. Number of patients in the registry corresponded almost perfectly with the National Register of Reimbursed Health Services.
Keywords: completeness; Czech republic; registry; pacemaker; mortality; implantation